What translatable knowledge from dengue vaccine design can we pass onto future anti-parasitic vaccine development? - Anon Srikiatkhachorn (My University, 2020)
KEYWORDS: Denguedengue vaccinesantibodyantibody dependent enhancementcell-mediated immunityparasite vaccines
Keywords: Dengue vaccine; Mosquito-borne diseases and control